Tingkat Kecemasan Kognitif dan Keyakinan Diri Para Atlet dari Berbagai Peringkat Perwakilan - Barnabas, Vincent A.; Mahamood, Yahaya (Faculty of Psychology, Universitas Surabaya, 2009)
Low self-confidence athletes usually experienced a high level of cognitive anxiety. Athletes’ performance level in sport was also found to be related to their cognitive anxiety and self- confidence. Research on cognitive anxiety and self-confidence of different categories of athletes’ level of performance, however is very limited. Hence, this research was conducted to investigate the influence of cognitive anxiety and self-confidence on performance of athletes of various categorical representations. The extent to which self-confidence influence cognitive anxiety among athletes was also examined. Nine hundred and eighteen Malaysian athletes were selected to complete Competitive State Anxiety Inventory 2 (CSAI-2). The findings reveal that national level athletes show a higher level of self-confidence but a lower cognitive anxiety level. Athletes representing school and university, on the other hand experienced a higher level of cognitive anxiety and lower level of self- confidence. Atlet yang rendah tahap keyakinan dirinya biasanya akan mengalami tahap kecemasan kognitif yang tinggi. Prestasi para atlet juga didapati berkait dengan tahap kecemasan kognitif dan keyakinan diri. Kajian tentang tahap kecemasan kognitif dan keyakinan diri di kalangan atlet pelbagai wakilan bagaimanapun boleh dikatakan amat kurang. Dengan itu kajian ini dilakukan untuk melihat kaitan tahap kecemasan kognitif dan keyakinan diri para atlet dari pelbagai wakilan. Kajian ini juga mengidentifikasi tahap keyakinan diri dan kecemasan kognitif para atlet yang terlibat. Sejumlah 918 atlet dipilih untuk menjawab kuesioner Competitive State Anxiety Inventory 2 (CSAI-2). Hasil kajian menunjukkan atlet negara (atlet nasional) bukan saja memiliki tahap keyakinan diri yang tinggi tetapi juga tahap kecemasan kognitif yang rendah. Sebaliknya atlet yang mewakili sekolah dan universitas mengalami tahap kecemasan kognitif yang lebih tinggi dan keyakinan diri yang lebih rendah.